The significance of fake news in modern media : A theoretical approach - Habeeb Malalla Ibrahim; Hoshyar Modafar Ali (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
The paper deals with the concept of fake news, which bears the characteristics of lying, fabrication, and forgery, and its role in modern media, whether the usual media or digital and interactive media, by defining its implications, characteristics, and detection mechanisms by investigative standards, digital tools, and programs, and investigating the origins of materials, images, videos, and those to whom the news is attributed with their words and actions. Fake news bears the connotations of crises and conflicts amidst a torrent of daily news, following the spread of the Corona epidemic, for example. The paper concluded that the platforms for publishing pictures and videos promoted the rooting of fake news, fake pictures, and fake videos and that fake news affected the structures of both traditional and digital interactive media systems. Fake news also stems from the desire to harm countries, policies, trends, and moral human tendencies by surrounding them with falsehoods and fabrications. On the other hand, social media has contributed to the emergence of fake news. On the other hand, social media platforms such as YouTube, Instagram, Snapchat, TikTok, Twitter, and Facebook did not make sufficient efforts to remove fake news, which affected modern media, both traditional and digital.